UJI DAYA IIASIL DAN PERTUMBUHAN TANAMAN PADI (OX YZA SATIVA. L)VARIETAS IR 64 PADA BERBAGAI TARAI PEMUPUKAN TRI CALSIUM PIIOSPAT ( TCP 36 ) - Bambang Suryotomo; Anwar Fauzan (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2007)
The research was conducted in a wet rice field ini Bajongbata, Pemalang. The used method was experimental with agroup random plan or RAK and was repeatedly conducted three times. 4 degrees of Fosfat fertilizing experimented contained of : D1 (0KG TcP/Ha; D2 (50 Kg/Ha; D3(100 Kg/Ha); and D4 (150 Kg/Ha). The result of the research showed that the productivity and growth of variety rice degree TCP 36. This all was showed by all observed and analyzed components that had F score bigger than F ccore of table 1 %. The production of rice plant was determinedby some componenls, they were): lhe number of malai per clump,number of unhulled paddy (gabah) Per malai, and weight of1000 seeds (IRRI, 1970). This meant that the number of riceplant that had many malai per clump, big number of unhulledpaddy per malai, and high weight of 1000 seeds would cause a high production. Based on the above three components, it couldbe also summarized rhat a good.t'ertilizel TCP 36 that wo ldgire the best pro.luctio was in a degree of 100 Kg/ha, and thatalso would produce 33,10 Kg per one Piece of feld of a dryunhulled paddy that was the same as 67,80 kw/ha. Keywords : Fosfat, Daya Hasil Padi, pertumbuhan Tanaman,tri calsium Phospat